Severe Aortic Stenosis Associated with Other Valve Diseases: Open Surgery or Percutaneous Treatment? - Sergio Moral; Marc Abulí; Esther Ballesteros; Pau Vilardell; Laura Gutiérrez; Ramon Brugada (Reviews in Cardiovascular Medicine, 2024)
Treatment decisions in the context of severe aortic stenosis (AS) associated with other valvular heart diseases (VHDs) have become a major challenge in recent years. Transcatheter aortic valve replacement (TAVR) in AS has increased significantly in younger patients with lower surgical risk, which has complicated the choice of the best treatment in cases of other associated valvulopathies. The most frequently associated lesions in this clinical scenario are mitral regurgitation (MR), mitral stenosis, and tricuspid regurgitation (TR). Furthermore, it should be noted that different percutaneous techniques are now available to accommodate any associated valvulopathies, which has considerably broadened the range of therapeutic options. The management of AS treated in isolation, especially by TAVR, has also shown that many cases of significant MR or TR are substantially reduced without any intervention. However, although some parameters have been described as potential risk factors in predicting the poor outcome of untreated VHDs, which cases will progress in a clinically more aggressive way remains uncertain. This review aimed to evaluate the most recent publications to provide the pathophysiology and prognosis of severe AS associated with other significant VHDs and to evaluate the best invasive therapeutic approach depending on the associated valvular disease.